"I want to remove your pain." Kinesiology and Physiotherapy in Paraguay. Its History - Evolution - Training Curriculum - Importance: Kinesiology and Physiotherapy in Paraguay 2023 (Journal on studies and research of academic knowledge, 2024)
This article focuses on Kinesiology and Physiotherapy in Paraguay. Its objective is a chronological description, its evolution and importance of its relevant events in our country. The research was qualitative. It was based on a bibliographic review and an analysis of documents collected in a semi-structured way. Several information channels were studied: On the one hand, the texts and articles of Lic. Lelis Noelia Morales Clemotte, Lic. Loria C. Giménez and Lic. Marcos Almirón. On the other hand, access to information provided by various National Institutions. As well as, historiographical publications by the authors Dr. Mary Monte de López Moreira and Alfredo Boccia Paz. This exposed profession presents its value in the impact of the socio-historical context that marks a trend of rehabilitation service and giving itself its deserved place in national health.
Keywords: Paraguay; Kinesiology; Physiotherapy; Training Curriculum; History